2019
DOI: 10.3390/ijerph16132263
|View full text |Cite
|
Sign up to set email alerts
|

Role of Manganese Oxyhydroxides in the Transport of Rare Earth Elements Along a Groundwater Flow Path

Abstract: Rare earth elements (REE) are known to be emerging contaminants in hydrosphere, but roles of hydrous manganese oxyhydroxides (HMO) in REE transport in groundwater remains unknown. In this study, groundwater was sampled along a flow path in the North China Plain to determine the behavior of REE surface complexation to HMO by a modeling and field study approach. Results show that the proportion of neodymium (Nd) complexed by HMO ranges from 0.2% to 95.8%, and from 0.3% to 99.6% in shallow groundwater and deep gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Fe, Mn) oxides (Yu et al, 2017). Results of our recent study showed that Ce precipitation from oxic aqueous solution was more likely to occur in the piedmont aquifers where low-Fe/Mn-concentration groundwater prevailed (Liu et al, 2019a), though no pronounced positive Ce anomalies were commonly observed in the piedmont aquifer sediments. Thus, both positive and negative Ce anomalies, and no Ce anomalies can be found in solid phases in nature, as the results shown in present study.…”
Section: Ree Fractionation Patternsmentioning
confidence: 75%
“…Fe, Mn) oxides (Yu et al, 2017). Results of our recent study showed that Ce precipitation from oxic aqueous solution was more likely to occur in the piedmont aquifers where low-Fe/Mn-concentration groundwater prevailed (Liu et al, 2019a), though no pronounced positive Ce anomalies were commonly observed in the piedmont aquifer sediments. Thus, both positive and negative Ce anomalies, and no Ce anomalies can be found in solid phases in nature, as the results shown in present study.…”
Section: Ree Fractionation Patternsmentioning
confidence: 75%
“…According to the statistical calculation results, the contents of As, Fe, and Mn in groundwater were from a native environment. Furthermore, the release of Fe and Mn from rock and soil to groundwater is controlled by nitrogen caused by agricultural activities [ 24 , 50 ]. Therefore, it can be concluded that F1 mainly reflects the influence of a native environment and agricultural activities.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in the groundwater chemical composition affect the mobility of different solutes. For example, the changes in salinity and the concentration of organic matter affect REE speciation and retention mechanisms. , In addition, the composition of the coastal aquifer might change spatially, which results in different retention mechanisms along paths of water flow …”
Section: Introductionmentioning
confidence: 99%
“…41,42 In addition, the composition of the coastal aquifer might change spatially, which results in different retention mechanisms along paths of water flow. 53 The main objective of this study is to explore the mechanisms that control the mobility and retention of REEs in different coastal aquifer materials at variable salinities. These goals are motivated by the fact that the production and use of REEs have grown significantly over the last decades, thus raising the potential for increased environmental contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation